(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Sorel cement (magnesium oxychloride cement, MOC) is an eco-friendly and high-strength binding material with potential applications in the production of cladding tiles. However, its durability and water resistance remain key challenges. This study explores the impact of incorporating different industrial and plastic wastes into MOC mortar to enhance its mechanical and durability properties. Waste materials such as polyethylene (PE), glass powder, and fly ash were introduced into the MOC mixture, and their effects on compressive strength, water resistance, and surface quality were analyzed. The findings indicate that specific waste additives improve the performance of Sorel cement-based cladding tiles, making them more suitable for construction applications.